2008
DOI: 10.1128/cvi.00476-07
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with aPseudomonas aeruginosa1244 Pilin Provides O-Antigen-Specific Protection

Abstract: The O antigen is both a major structural outer membrane component and the dominant epitope of most gram-negative bacteria. Pseudomonas aeruginosa 1244 produces a type IV pilus and covalently links an Oantigen repeating unit to each pilin monomer. Here we show that immunization of mice with pure pilin from strain 1244 by use of either the mouse respiratory model or the thermal injury model resulted in protection from challenge with a pilus-null O-antigen-producing 1244 mutant. These results provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 46 publications
0
38
0
1
Order By: Relevance
“…We have shown that the P. aeruginosa strain 1244 pilin-bound O-antigen repeating unit is immunogenic (9) and that this structure provides O-antigen-specific protection (29). A T-cell-dependent response against this saccharide is indicated by the strong IgG reaction seen (29). This vaccine target is not limited to the lipopolysaccharide of P. aeruginosa, since the minimal PilO glycan requirement is found in the O-antigen repeating units of many bacterial pathogens (14,28).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have shown that the P. aeruginosa strain 1244 pilin-bound O-antigen repeating unit is immunogenic (9) and that this structure provides O-antigen-specific protection (29). A T-cell-dependent response against this saccharide is indicated by the strong IgG reaction seen (29). This vaccine target is not limited to the lipopolysaccharide of P. aeruginosa, since the minimal PilO glycan requirement is found in the O-antigen repeating units of many bacterial pathogens (14,28).…”
Section: Discussionmentioning
confidence: 98%
“…Immunization with either pili (38) or O antigen (15,40,52) from P. aeruginosa has been shown to be protective, as determined in murine models. We have shown that the P. aeruginosa strain 1244 pilin-bound O-antigen repeating unit is immunogenic (9) and that this structure provides O-antigen-specific protection (29). A T-cell-dependent response against this saccharide is indicated by the strong IgG reaction seen (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This immunization route was selected because previous studies showed robust mucosal and systemic antibody production in response to alternative Pseudomonas vaccines. 20,21 Serum was collected from mice 42 days post-immunization. Mice that had been immunized with LVS / pGFLI produced robust levels of antibodies specific for P. aerugionsa (P < 0.05) compared to animals treated with PBS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the more immediate future, studies should investigate whether immunization with F. tularensis / pGFLI protects against a lethal P. aeruginosa infection using the appropriate animal model such as the murine cystic fibrosis model or the burn mouse model. 21,32 …”
Section: Discussionmentioning
confidence: 99%